DAMPAK PERKEMBANGAN PARIWISATA MINAT KHUSUS SNORKELING TERHADAP LINGKUNGAN: KASUS DESTINASI WISATA KARIMUNJAWA - Priyanto, Sabda Elisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2016)
The study will analyze the impact of tourism by the type of special interest tourism to the environment. Impact on the coast and islands, the impact on vegetation, the impact wildlife, and the impact on urban areas and rural areas. Positive impact on the coast and the island is the effort for preservation and conservation of coral reefs, reef fish, giant clams and turtles, and encouraged to make environmentallyfriendly tourism activities. The negative impact is a damage to coral reefs from snorkeling activities, and the loss of traditional land allotment to the beach. The positive impact on vegetation is their attempt to biodiversity and conservation of vegetation typical of Publications, and reforestation activities is to replant mangrove. Negative impacts on vegetation is illegal logging and the clearing of trees to increase tourist attraction as supporters of the main activities. commercialization of the plant for souvenirs. Positive impact on wildlife is their conservation, preservation, and biodiversity, the breeding of animals and relocating the animals to their natural habitat. The negative impact is going hunting animals as souvenirs and tourist consumption, harassment of wildlife photography, animal exploitation for pertujukan, changes in animal instincts, and the migration of animals. Positive impact on urban areas and rural areas is happening arrangement karimunjawa towns and villages, and their empowerment. The negative impact of pressure on the land for the opening of a new tourist attraction, there are exchange in the function of residential land into commercial land, and the occurrence of traffic congestion, noise pollution, air pollution, and pollution aesthetics. Keywords: Environmental Impact, Tourism, Snorkeling